Yahoo Web Search

  1. a . k equals m divide by n. b. V equals k divided by the product of w and h. c. E ...

    2 Answers · Science & Mathematics · 16/03/2013

  2. a ) v (1-w)+w( v -1) v - v w+w v -w since -vw+wv=0 ans .. v -w b) m ^2-( k - m )^2 over k , k =/ 0 m ^2-( k ^2-2km+ m ^2) over k m ^2- k ^2+2km- m ^2 over k ...

    6 Answers · Science & Mathematics · 25/02/2011

  3. ... 4. ~( K & ~L) v (~L & M ) Premise 5. K 1,2 Disjunctive Syllogism... M 10 Simplification 1. A v B Premise 2. C...

    1 Answers · Science & Mathematics · 05/11/2011

  4. I' m assuming * is the...vector w, and assume that u and v have the same length n. You...the sum, from j = 1 to n, of ( k u_j) v _j [from the definition of...multiplication of real numbers: a single number k can be...

    1 Answers · Science & Mathematics · 02/05/2011

  5. ...in V _ m . Then since y is the limit of (y_i), there is a k > 0 such that y_n is in V _ m for all n >= k . Case 1: k <= m . Then y_ m ...

    2 Answers · Science & Mathematics · 16/10/2010

  6. ... by 2 KA² = MVi² A² = ( M / K )Vi² A = √( M / K )Vi ← this assumes that i is an index on V , not √(-1)

    2 Answers · Science & Mathematics · 18/06/2015

  7. ... So, B = 9.8/ k Now add both solutions: v = A e^kt/ m + 9.8/ k And use the initial conditions: v (0) = v (0) to evaluate A ...

    4 Answers · Science & Mathematics · 31/12/2006

  8. Essentially you want to write the integral as: ( m / k )*dv / [ mg/ k - v ^2] And replace mg/ k with a ^2. The easiest method is to get the hyperbolic trig function directly...

    1 Answers · Science & Mathematics · 21/06/2007

  9. k - 16= 7 k = 23 y + 12 = -10 y= 22 x + 8 = -1 x= -9 v + 13 = -11 v = -24 p + 14 = -1 p= -15 h - 9 = 12 h= 21 c + 5 = 2 c= -3 a - 12 = -19 a = -7 q + 3 + -5 q = -8 m - 10 = 4 m = 14 j+11= 4 j= -7

    5 Answers · Science & Mathematics · 27/09/2011

  10. mv' = -mg -kv v ' + ( k / m ) v = -g d/dt [ e^(kt/ m ) v ] = -ge^(kt/ m ) e^(kt/ m ) v = -g ∫e^(kt/ m ) dt e^(kt/ m ...kt/ m ) - gm/ k Or using separation of variables: ∫ dv / (-g - ( k / m ) v ) = ∫ dt - m / k ln(gm + kv) = t + c ln(gm + kv) = -kt/ m + c gm + kv = ce^(-kt/ m ) v ...

    1 Answers · Science & Mathematics · 29/09/2009

  1. Try asking your question on Yahoo Answers